Eyewitness to Irish history - Ellis, Peter Berresford (John Wiley & Sons, 2004)
The book covers more than twenty historical events covering three millennia in 300 pages.The book is well referenced and has a great bibliography. It includes many primary sources and eyewitness accounts.